Comparative study of interactive systems in a museum - Michael-Grigoriou, Despina; Pelekanos, Nectarios; Chrysanthou, Isabelle; Zaharias, Panagiotis; Hadjigavriel, Loukia L.; Chrysanthou, Yiorgos (My University, 2010)
Museums research new ways to offer positive experience to the visitors and encourage them to return, using modern communication and learning tools. To the effect, technologically advanced interactive ICT systems, are placed in modern-day museums. In this paper we describe and compare six different types of museum exhibits, one traditional and five interactive ICT exhibits. The five interactive ICT systems offer different types and level of digital information, different interaction constraints and different types of activities. The exhibits, which are located in the Leventis Municipal Museum in Nicosia, are the following: a traditional map learning activity, a virtual tour projection, a multi-touch table application and three different augmented reality applications. We evaluated the experience of young users with the exhibits and conclude that the experience scores top marks for the interactive ICT systems.
Keywords: Interaction; Museum; Comparative study; Video projection; Multi-touch table; Augmented reality